2015
DOI: 10.1016/j.comptc.2015.06.029
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cluster transition-metal bonding in oblato-nido dimetallaboranes unveiled by topological analysis

Abstract: The bonding situation for the oblato-nido dimetallaboranes (CpV)(2)B5H11 and (Cp*T)(2)B5H5+x, where T= Ta, Cr, Mo, W, Re and Cp*= C5Me5, was analyzed using the corresponding model series with Cp* replaced by the cyclopentadienyl C5H5. The application of different bonding indicators revealed that both through-space and through-bond (via boron atoms of the ring) interactions account for a substantial metal-metal bond. (C) 2015 Elsevier B.V. All rights reserved

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In clusters 2-4, computations indicated that the 11 B NMR chemical shifts of the boron atoms attached directly to the metal atoms (B2, B4, and B3, Figure 2) show a large systematic shift to higher field, whereas the chemical shifts at upper field for the boron atoms connected to the metal atoms via M−H−B bridged bonds (B1 and B5, Figure 2) hardly deviate from Cr to Mo to W species. The nature of the M-M interaction in clusters 2-6 and 8 was further probed using Cp-analog models employing the electron density and its derivatives within the framework of the QTAIM method and the aid of bonding indicators [70]. Results revealed that both through-space and through-bond (via boron atoms of the ring) interactions account for a substantial metal-metal interaction with a covalent bond order around 1.…”
Section: Electronic Structurementioning
confidence: 99%
See 1 more Smart Citation
“…In clusters 2-4, computations indicated that the 11 B NMR chemical shifts of the boron atoms attached directly to the metal atoms (B2, B4, and B3, Figure 2) show a large systematic shift to higher field, whereas the chemical shifts at upper field for the boron atoms connected to the metal atoms via M−H−B bridged bonds (B1 and B5, Figure 2) hardly deviate from Cr to Mo to W species. The nature of the M-M interaction in clusters 2-6 and 8 was further probed using Cp-analog models employing the electron density and its derivatives within the framework of the QTAIM method and the aid of bonding indicators [70]. Results revealed that both through-space and through-bond (via boron atoms of the ring) interactions account for a substantial metal-metal interaction with a covalent bond order around 1.…”
Section: Electronic Structurementioning
confidence: 99%
“…The examples of this kind of M 2 B 5 species mostly range among the early transition metals such as group 5 in [(CpV) 2 B 5 H 11 ] [ 58 ] and [(Cp*Ta) 2 B 5 H 11 ] [ 59 ], group 6 in [(Cp*M) 2 B 5 H 9 ] (M = Cr, Mo, W) [ 60 , 61 , 62 , 63 , 64 , 65 ], and group 7 in [(Cp*Re) 2 B 5 Cl 5 H 2 ] [ 24 ] (Cp = C 5 H 5 , Cp* = C 5 Me 5 ). Due to their unique structure, thorough theoretical studies were performed by us and others in order to get some insight into their electronic structure and chemical bonding [ 66 , 67 , 68 , 69 , 70 ]. Later, many heterometallic [ 63 , 71 , 72 , 73 , 74 ] and chalcogenated derivatives of oblatonido-M 2 B 5 [ 75 , 76 , 77 , 78 ] were reported in the literature, which are isostructural as well as isoelectronic.…”
Section: Introductionmentioning
confidence: 99%
“…29 The experimentally observed oblatocloso structures, with the rhenium atoms located at approximately antipodal vertices, were very gratifyingly found to be the lowest energy structures. Subsequent theoretical studies by Halet and coworkers 30,31 have provided further insight into the metal-metal bonding in such structures. In addition, higher energy Cp 2 Re 2 B nÀ2 H nÀ2 isomers were found with adjacent rhenium vertices and short Re-Re distances suggesting surface multiple rhenium-rhenium bonds.…”
Section: Introductionmentioning
confidence: 99%